Effect of MoO3 on Na2O–B2O3–CdO–ZnO glasses: Applications in optoelectronics, communication devices, and radiation shielding. Issue 7 (1st April 2023) - Singh, R. Umamaheswara; Sekhar, K. Chandra; Alzahrani, Jamila S.; Alrowaili, Z.A.; Shareefuddin, Md.; Purushotham, Y.; Olarinoye, I.O.; Al-Buriahi, M.S.
Abstract: The current study focuses on the physical and structural aspects of B2 O3 –CdO–ZnO–Na2 O glasses that have been reinforced by MoO3 ions. The samples were experimentally prepared using a melt quenching procedure, and then the absence of strong peaks in the XRD spectra confirms their amorphous nature. A variety of optical, Raman, and radiationshielding qualities were evaluated and described. The structural changes in the material were investigated using FTIR and Raman spectra. The density of the samples rose when MoO3 was added, implying that BO3 was transformed into BO4 units. The transition of Mo 6+ to Mo 5+ ions is responsible for the reduction in band gap in these glasses. Because of the vacancy generated by the oxygen units, the Urbach energy increased, implying the generation of additional defects. The presence of diverse structures present in the structure of the glass was revealed by FTIR and Raman spectra, such as MoO6, BO3, BO4, metaborates, pyroborates, and so on. The transition of BO3 to BO4 units, which is crucial in density analyses, was also corroborated by Raman spectra. Using FLUKA simulation and XCOM estimations, the mass attenuation coefficient of the glasses improved with the amount of MoO3 . At 15 keV, the half-value layer of 0.0103 cm, 0.01019 cm, 0.01016 cm, 0.0101 cm, and 0.01005 cm was obtained for glasses with an MoO3 concentration of 0, 0.5, 1, 1.5, and 2.0 mol% respectively. The optimum MoO3 concentration for fast and thermal neutron cross-sections was 0.5 and 2.0 mol% respectively. The glasses are viable materials for environmentally friendly and transparent radiation barriers in nuclear facilities.